(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
this research aims at a number of objectives including Developing the tax examination process and raise its efficiency without relying on comprehensive examination method using some statistical methods in the tax examination and Discussing the most important concepts related to the statistical methods used in the tax examination and showing its importance and how they are applied. the research represents an applied study in the General Commission of taxes. In order to achieve its objectives the research has used in the theoretical side the descriptive approach (analytical), and in the practical side Some statistical methods applied to the sample of the final accounts for the contracting company (limited) and the pharmaceutical industry (private contribution), The research has reached set of results that:The statistical methods work on developing the tax examination process since the statistical sampling can determine the extent of reliance on taxpayer accounts submitted in his tax endorsement without conducting a comprehensive examination and The statistical Analysis procedures represented by time-series, regression and correlation work in determining the relationship among the variables in the tax endorsement and vrifying the reasonableness of its figures.